Development Evaluation in PEO and its Impact - Planning Commission (Planning Commission, 2004)
Plan formulation, plan administration and plan evaluation form a sequence of planning process-interlinked and integrated. Feedback through evaluation results is an important requirement for assessing the performance, comparing the intended with actuals and using the information as guide for improved policy/program/project planning. The Principle of systematic feedback is of prime importance for the self-governing goal seeking systems. Programme Evaluation Organisation in Planning Commission has been providing vital ingredient of lessons from development experience for systematic improvement of the planning and policy formulation process. Recently, the domain of activity of PEO has enlarged significantly. This includes, among other things, providing technical support to various Ministries, Divisions of Planning Commission and State Governments, organising training programmes and scrutinizing study designs/proposals under SER Unit of Planning Commission. The experience in evaluation methods and practices that PEO has attained over the years is being shared with different Government and Non-Government Organisations. The year 2003-04 has been particularly eventful with significant increase in the number of schemes being evaluated and the support services offered by PEO to different institutions/organisations.
Programme Evaluation Organisation Planning Commission Government of India